2023
DOI: 10.1037/pspp0000445
|View full text |Cite
|
Sign up to set email alerts
|

Do people agree on how they and others are acting? Examining the degree of target–observer and observer–observer agreement about current behavior as it changes across situations.

Abstract: The purpose of the present research was to test the level of agreement between targets and observers both at any given moment and as the targets’ current behavior (assessed as personality states) change across moments. Ninety-seven target participants participated in 22 different activities across 20 1-hour long sessions in a laboratory setting while reporting their current behavior, and their behavior was evaluated by 183 observers (total of 3,493 target self-reports, 2,973 of which had a corresponding observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 121 publications
0
2
0
Order By: Relevance
“…Note, however, that our sample of observers included two different types of observers (i.e., supervisors and students), and analyses across these different rater sources (i.e., supervisor-rated personality variability predicting student-rated performance) yielded various significant effects (see Table 3), suggesting that effects may not be solely due to common rater biases (Podsakoff et al, 2003). Furthermore, recent experience sampling research has demonstrated significant agreement among different observers regarding others' personality states (Jayawickreme et al, 2023;Leikas & Lönnqvist, 2022), suggesting that other-ratings of personality states do not merely capture raters' own idiosyncratic perceptions but rather reflect actual observable behaviors. Although our overall conclusions were strengthened by a set of additional analyses that showed mostly similar results when we accounted for curvilinear effects of mean-level personality (cf., Jones et al, 2017), the main absence of cross-method effects does indicate a lack of robustness of the current findings.…”
Section: Discussionmentioning
confidence: 98%
“…Note, however, that our sample of observers included two different types of observers (i.e., supervisors and students), and analyses across these different rater sources (i.e., supervisor-rated personality variability predicting student-rated performance) yielded various significant effects (see Table 3), suggesting that effects may not be solely due to common rater biases (Podsakoff et al, 2003). Furthermore, recent experience sampling research has demonstrated significant agreement among different observers regarding others' personality states (Jayawickreme et al, 2023;Leikas & Lönnqvist, 2022), suggesting that other-ratings of personality states do not merely capture raters' own idiosyncratic perceptions but rather reflect actual observable behaviors. Although our overall conclusions were strengthened by a set of additional analyses that showed mostly similar results when we accounted for curvilinear effects of mean-level personality (cf., Jones et al, 2017), the main absence of cross-method effects does indicate a lack of robustness of the current findings.…”
Section: Discussionmentioning
confidence: 98%
“…Note, however, that our sample of observers included two different types of observers (i.e., supervisors and students), and analyses across these different rater sources (i.e., supervisor-rated personality variability predicting student-rated performance) yielded various significant effects (see Table 3), suggesting that effects may not be solely due to common rater biases (Podsakoff et al, 2003). Furthermore, recent experience sampling research has demonstrated significant agreement among different observers regarding others’ personality states (Jayawickreme et al, 2023; Leikas & Lönnqvist, 2022), suggesting that other-ratings of personality states do not merely capture raters’ own idiosyncratic perceptions but rather reflect actual observable behaviors. Although our overall conclusions were strengthened by a set of additional analyses that showed mostly similar results when we accounted for curvilinear effects of mean-level personality (cf.…”
Section: Discussionmentioning
confidence: 99%